2012
DOI: 10.5194/hess-16-1595-2012
|View full text |Cite
|
Sign up to set email alerts
|

Changes in discharge and solute dynamics between hillslope and valley-bottom intermittent streams

Abstract: Abstract. To gain understanding on how alluvial zones modify water and nutrient export from semiarid catchments, we compared monthly discharge as well as stream chloride, carbon, and nitrogen dynamics between a hillslope catchment and a valley-bottom catchment with a well-developed alluvium. Stream water and solute fluxes from the hillslope and valley-bottom catchments showed contrasting patterns between hydrological transitions and wet periods, especially for bio-reactive solutes. During transition periods, s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 53 publications
(67 reference statements)
4
8
2
Order By: Relevance
“…The relatively low ET values, together with the fact that the riparian forest occupied a small area of the catchment (6 %), resulted in a minimal contribution (4.5 %) of riparian transpiration to the annual water budget for this catchment. This estimate is similar to values reported for tropical (Cadol et al, 2012), temperate (e.g., Petrone et al, 2007;Salemi et al, 2012), and Mediterranean (e.g., Bernal and Sabater, 2012;Folch and Ferrer, 2015;Wine and Zou, 2012) systems, while being several folds lower than values reported for semiarid and dry land regions (Contreras et al, 2011;Dahm et al, 2002;Doble et al, 2006) (Fig. 6).…”
Section: Influence Of Riparian Et On Stream and Riparian Groundwater supporting
confidence: 89%
See 3 more Smart Citations
“…The relatively low ET values, together with the fact that the riparian forest occupied a small area of the catchment (6 %), resulted in a minimal contribution (4.5 %) of riparian transpiration to the annual water budget for this catchment. This estimate is similar to values reported for tropical (Cadol et al, 2012), temperate (e.g., Petrone et al, 2007;Salemi et al, 2012), and Mediterranean (e.g., Bernal and Sabater, 2012;Folch and Ferrer, 2015;Wine and Zou, 2012) systems, while being several folds lower than values reported for semiarid and dry land regions (Contreras et al, 2011;Dahm et al, 2002;Doble et al, 2006) (Fig. 6).…”
Section: Influence Of Riparian Et On Stream and Riparian Groundwater supporting
confidence: 89%
“…Thus, riparian trees could affect the strength, location, and duration of the predominant flow path, and consequently, influence the capacity of riparian zones to reduce N not only from upland groundwater inputs, but also from stream water. In this line of thought, previous studies have reported decreases in stream N concentration along losing stream reaches attributed to N uptake at the stream-riparian edge (Bernal and Sabater, 2012;Dent et al, 2007;Rassam et al, 2006). Yet, there has been little research focused on the influence of riparian ET on upland-riparian-stream hydrological exchange and its potential to promote variations in stream N concentrations and fluxes.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…Drying and its consequences, such as disconnection of flow paths laterally and longitudinally, as well as longer water residence times (Fisher, Grimm, Martí, & Gómez, 1998;Harvey, Conklin, & Koelsch, 2003) provoked a decrease in SRP and NO 3 concentrations that is also observed in other studies from intermittent streams (Bernal & Sabater, 2012;Martí, Grimm, & Fisher, 1997;von Schiller et al, 2008). Additionally, in intermittent streams, the absence of surface flow can involve the diffusion of oxygen into the pore space of the hyporheic zone that triggers ammonia oxidation (Merbt et al, 2016).…”
Section: Nutrient Retention and Dom Mineralisation In The Hyporheicsupporting
confidence: 52%